Simulated Freedom in the Metaverse Narrative: Animation and Virtuality on the Roblox Platform - Iparraguirre-Bernaola, Alvaro (2023)
The constant development of digital media, particularly the contributions of video games in terms of animation and immersion, has favored the emergence of new spaces for communication, generating virtual environments like the metaverse. This research aims to recognize the possibilities and limitations in the limitless freedom presented by the metaverse to establish the level of control designers have over users and vice versa. The research proposes a qualitative approach, studying selected literature and analyzing avatars and mediation systems in the Vans World and Nikeland experiences within Roblox. This analysis makes evident the interactive characteristics of these environments and reveals the narrative produced from the construction of simulated freedom. The research results indicate that the simulated freedom proposed by the metaverse does not differ from the conditioning and control already employed in other media; as the possibilities grow, so does control, following the trends imposed by virtual technology, which creates the illusion of having what one does not possess.